2023
DOI: 10.1021/acs.langmuir.2c03330
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Ciprofloxacin from Water by a Potassium Carbonate-Activated Sycamore Floc-Based Carbonaceous Adsorbent: Adsorption Behavior and Mechanism

Abstract: In this study, a porous carbonaceous adsorbent was prepared from sycamore flocs by pyrolysis method and K2CO3 activation. The effects of preparative conditions of the material on its adsorptive property were explored. The optimal material (SFB2‑900) was obtained with a K2CO3/biochar mass ratio of 2:1 at an activation temperature of 900 °C, possessing a huge surface specific area (1651.27 m2/g). The largest adsorption capacity for ciprofloxacin on SFB2‑900 was up to 430.25 mg/g. The adsorption behavior was well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Howe tion of KHCO3 did not significantly affect the sorption of OFL on WBS5. A p also indicated that the hydrolysis of carbonate slats could produce a large a in the solution [63], thereby inhibiting the ciprofloxacin sorption. These gested that the co-existing K + did not significantly affect OFL sorption on while HCO3 − may increase the solution pH, and thus decrease the OFL sorp The impact of ions on FQs has been previously discussed.…”
Section: Effect Of K-containing Salts On Ofl Sorptionmentioning
confidence: 99%
“…Howe tion of KHCO3 did not significantly affect the sorption of OFL on WBS5. A p also indicated that the hydrolysis of carbonate slats could produce a large a in the solution [63], thereby inhibiting the ciprofloxacin sorption. These gested that the co-existing K + did not significantly affect OFL sorption on while HCO3 − may increase the solution pH, and thus decrease the OFL sorp The impact of ions on FQs has been previously discussed.…”
Section: Effect Of K-containing Salts On Ofl Sorptionmentioning
confidence: 99%
“…Oil spills in the ocean and oil cleanup have turned into a pressing environmental issue . The separation procedure may be more challenging due to the presence of emulsified oil, water-soluble dyes, insoluble oil, and oil-soluble colors in the effluent. As a result, creating an emulsion separation surface is now a pressing concern in this field of study. However, the majority of conventional techniques for separation are ineffective. , Nature has demonstrated extraordinary design skills for biomaterials with unique wettability during millions of years of evolution by meticulously regulating the surface’s chemical composition and geometrical structure. Due to the fast development of special wettability surfaces, biomimetic materials with super-wettability have recently shown tremendous potential for emulsion separation. The formation of super-wettability is significantly influenced by the inherent contact angles of oil (θ O ) and water (θ W ) .…”
Section: Introductionmentioning
confidence: 99%